Uso da tomografia computadorizada de feixe cônico modificada para avaliação padronizada em tecidos ósseo e gengival na reabilitação com implantes imediatos - Bridi, Márjorie das Posses (2019)
Introduction: The use of imaging exams to evaluate aesthetic parameters in dental rehabilitation with dental implants is still incipient. Purpose: To evaluate the preoperative dentogengival unit and changes in the bone and gingival tissues after rehabilitation with implants and immediate provision by the technique Soft Tissue Cone-Beam Computed Tomography (ST-CBCT) and to compare the clinical and tomographic characteristics of the gingival tissue. Materials and Methods: This is a series of cases of 06 patients submitted to immediate and temporary implant rehabilitation in the aesthetic maxilla region. The following measurements were made on the vestibular aspect of the images obtained by the ST-CBCT in the pre and postoperative period of 03 and 06 months: Bone Thickness (EO), Bone Height (AO), Gingival Thickness (EG) and Gingival Height (AG). The clinical gingival biotype obtained by periodontal probing was compared to tomographic EG. Data were submitted to descriptive analysis. Results: An increase was recorded EO increased in patients 01 (+1.03mm), 02 (+0.66mm) and 06 (+0.06mm) and reduced in cases 03 (-0.17mm), 04 (-0.41mm) and 05 (-0.38mm). In patients 02 and 03, after bone remodeling with AO reduction, the buccal bone was at the level of the implant platform; in all other cases the implants remained infra-bony. The EG increased in cases 01 (+0.30 mm), 02 (+0.80 mm), 03 (+0,68mm) and 06 (+0.74mm), and there was a reduction in AG of cases 01 (-0.30 mm), 03 (-0.04mm) and 05 (-0.06mm). Conclusions: ST-CBCT has been shown to be a noninvasive instrument for evaluating bone and gingival tissues in the pre and postoperative rehabilitation with immediate implants and allowed standardized measurement of peri-implant tissues in the long term.